Mast Cell Interaction with Neutrophils in Human Gastric Carcinomas: Ultrastructural Observations - Antonio Ieni; Valeria Barresi; Giovanni Branca; Rosario Alberto Caruso; Giovanni Tuccari (Analytical Cellular Pathology)
Aim. The role of mast cells in cell-cell immune interactions has received increasing attention, although their functional interaction with neutrophils still remains to be clarified in tumors. The aim of the present study was to investigate the association between mast cells and neutrophils in a series of gastric carcinomas (GC). Patients and Methods. 52 surgically resected GC specimens were routinely processed for both light and electron microscopy. Only cases showing both mast cells and neutrophils in the tumor stroma were considered in the analysis. Results. Only 9 GC (M : F = 5 : 4; age range: 50–82 years) showed both mast cells and neutrophils in the tumor stroma. At ultrathin sections, we identified heterotypic aggregation and intermingling of mast cells and neutrophils. Mast cells had mature phenotype and showed full complement of granules with homogeneous, scroll, particle, and mixed pattern. In addition, we found normal-appearing or early apoptosis showing neutrophils. Conclusion. Our histological findings showed the likely interaction between mast cells and neutrophils in GC. We hypothesize that the granular content of mast cells may be released in small quantity through a mechanism called “kiss-and-run fusion,” which is alternative to well-known massive anaphylactic or piecemeal degranulation.